Silariang dalam Perspektif Hukum Islam dan Hukum Adat - Saleh Saleh; Jumadil Jumadil; Agus Cahyadi; Amrul Amrul (Al-Azhar Islamic Law Review, 2021)
This study aims to determine silariang from the perspective of Islamic law and customary law in Bontocani District, Bone Regency. This research is a type of normative legal research using a juridical approach and a sociological approach. This study indicates that crossbreeding in Islamic law is invalid because the marriage is legally flawed and does not fulfill the legal requirements of marriage, namely without the consent of the guardian. In other words, a marriage that is held in a crossbreeding marriage is considered null and void. While silariang in Customary Law in the Bugis community in Bontocani District, Bone Regency is seen as an act that brings Siri’ (shame). Those who commit such violations may be subject to sanctions, either in the form of light sanctions such as expulsion and expulsion or severe sanctions, namely being killed